Secondary batteries and electronic devices
By applying different types of negative electrode active materials in a region-based manner on the negative electrode sheet of the lithium-ion battery, the problem of graphite peeling caused by co-embedding of solvents in the non-embedded lithium zone under low temperature conditions is solved, and a higher charging speed, Coulomb efficiency and cycle life are achieved.
Patent Information
- Application Number
- CN202411896836.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-01
AI Technical Summary
Under low temperature conditions, co-embedding of non-lithium-embedded solvents in lithium-ion batteries leads to graphite peeling, resulting in abnormal pitting of electrode components, affecting the performance and life of the battery.
By coating different negative electrode active materials in a region-by-region manner on the negative electrode sheet, artificial graphite or natural graphite with a cladding layer is used in the lithium embedded region, and artificial graphite or natural graphite is used in the non-lithium embedded region, increasing the layer spacing, increasing the diffusion rate of lithium ions, and forming a stable SEI film to reduce side reactions.
It improves the charging speed and Coulomb efficiency of lithium-ion batteries, reduces the risk of graphite peeling caused by the co-embedding of solvents in the non-embedded lithium area, and extends the cycle life of the battery.
Smart Images

Figure CN119742415A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries represented by lithium-ion batteries have outstanding characteristics such as high energy density, long cycle life, low pollution, and no memory effect. At present, fast-charging graphite with a coating layer has become the preferred negative electrode active material in lithium-ion batteries because it can form a protective film on the surface of graphite particles, reduce side reactions during the cycle, and thus improve the performance and cycle life of lithium-ion batteries.
[0003] However, when fast-charging graphite with a coating layer is used as the negative electrode active material, for the electrode assembly with a multi-ear structure, the film-forming quality of graphite in the negative electrode sheets in different areas is different. At low temperatures (temperature ≤ 10°C), the lithium ion desolvation ability is poor, and solvent co-embedding is prone to occur during the charge and discharge process. When the solvent co-embedding is severe, graphite peeling will occur, resulting in small protrusions or granular defects on the appearance of the electrode assembly, that is, abnormal appearance pitting. Summary of the invention
[0004] The purpose of this application is to provide a secondary battery that takes into account the fast charging performance and high coulombic efficiency of lithium-ion batteries while reducing the risk of graphite exfoliation caused by solvent co-intercalation in the non-lithium intercalation area of lithium-ion batteries. The specific technical solution is as follows:
[0005] It should be noted that in the invention content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0006] The first aspect of the present application provides a secondary battery, the secondary battery includes an electrode assembly of a winding structure, the electrode assembly includes a positive electrode sheet and a negative electrode sheet, in the winding structure, along the opposite direction of the winding direction of the electrode assembly, the winding start end of the negative electrode sheet exceeds the winding start end of the positive electrode sheet. The positive electrode sheet includes a positive electrode collector, the negative electrode sheet includes a negative electrode collector, along the length direction of the unfolded negative electrode sheet, and along the winding direction of the electrode assembly, the negative electrode collector includes a first section and a second section connected in sequence, in the winding structure, the first section is a portion of at least one surface of the negative electrode collector that is not opposite to the positive electrode collector, and the second section is a portion of both surfaces of the negative electrode collector that are opposite to the positive electrode collector. Wherein, the negative electrode sheet includes a first negative electrode material layer and a second negative electrode material layer arranged on the surface of the negative electrode collector, the first negative electrode material layer includes a first negative electrode active material, and the first negative electrode active material includes at least one of artificial graphite or natural graphite. The second negative electrode material layer includes a second negative electrode active material, the second negative electrode active material includes at least one of artificial graphite or natural graphite with a coating layer, the coating layer includes a coating material, and the coating material includes one of a carbon material, an oxide or a polymer. The first section is provided with the first negative electrode material layer on at least a portion of the surface facing the winding center of the electrode assembly, and the second section is provided with the second negative electrode material layer on at least a portion of the surface facing the winding center of the electrode assembly. The present application applies different negative electrode active materials on the negative electrode plate in a zone-by-zone manner. The lithium-intercalation zone uses artificial graphite and / or natural graphite with a coating layer as the negative electrode active material, which can increase the interlayer spacing, improve the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, thereby improving the charging speed and coulomb efficiency of the secondary battery; the non-lithium-intercalation zone uses artificial graphite and / or natural graphite as the negative electrode active material. Conventional graphite materials have a smaller interlayer spacing and fewer micropores in the microstructure, which is conducive to reducing the embedding of solvent molecules during the charging and discharging process, thereby reducing the risk of graphite exfoliation in the non-lithium-intercalation zone caused by solvent co-intercalation in the non-lithium-intercalation zone in the lithium-ion battery. Therefore, the secondary battery of the present application can effectively reduce the risk of graphite exfoliation in the non-lithium-intercalation zone caused by solvent co-intercalation in the non-lithium-intercalation zone in the lithium-ion battery while taking into account a higher charging speed and good coulomb efficiency.
[0007] In one or more embodiments, at least a portion of the surface of the first section facing away from the winding center of the electrode assembly is provided with a second negative electrode material layer, the positive electrode sheet includes a positive electrode material layer, and a positive electrode material layer is provided on a surface of the positive electrode current collector opposite to the second negative electrode material layer. Through the above arrangement, while reducing the risk of graphite stripping in the non-lithium intercalation region caused by solvent co-intercalation in the non-lithium intercalation region of the lithium-ion battery, it is beneficial to improve the charging speed and coulomb efficiency of the secondary battery.
[0008] In one or more embodiments, the width of the electrode assembly is L mm, and the length of the first section along the length direction of the unfolded negative electrode sheet is L1 mm, 1.5≤L1 / L≤2.5, 39.0≤L≤40.5. By regulating the values of L1 / L and L within the above range, different negative electrode active materials are coated on the negative electrode sheet in a zone-by-zone manner, which helps to reduce the embedding of solvent molecules during the charging and discharging process while taking into account a high charging speed and good coulombic efficiency, thereby reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-embedding in the non-lithium intercalation area of the lithium-ion battery, and at the same time helps to reduce the risk of the non-lithium intercalation area of the first section being too long, thereby reducing the energy density and kinetic performance of the secondary battery.
[0009] In one or more embodiments, the negative electrode current collector further includes a third section connected to the second section, and along the winding direction of the electrode assembly, the third section is a portion of at least one surface of the negative electrode current collector that is not opposite to the positive electrode current collector, and at least part of the surface of the third section facing away from the winding center of the electrode assembly is provided with a first negative electrode material layer, and at least part of the surface of the third section facing the winding center of the electrode assembly is provided with a second negative electrode material layer. Through the above arrangement, the lithium-intercalation region at the tail end of the negative electrode sheet uses artificial graphite and / or natural graphite with a coating layer as the negative electrode active material, and the secondary battery is beneficial to further reduce the risk of graphite exfoliation in the non-lithium intercalation region caused by solvent co-intercalation in the non-lithium intercalation region of the lithium-ion battery while taking into account a higher charging speed and good coulomb efficiency.
[0010] In one or more embodiments, the width of the electrode assembly is L mm, and the length of the third section is L2 mm along the length direction of the unfolded negative electrode sheet, 1.5≤L2 / L≤3.0, 39.0≤L≤40.5. By regulating the values of L2 / L and L within the above range, different negative electrode active materials are coated on the negative electrode sheet in a zone-by-zone manner, which is beneficial to reduce the embedding of solvent molecules during the charging and discharging process while taking into account a high charging speed and good coulombic efficiency, thereby reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-embedding in the non-lithium intercalation area of the lithium-ion battery, and at the same time, it is beneficial to reduce the risk of the non-lithium intercalation area of the third section being too long, thereby reducing the energy density and kinetic performance of the secondary battery.
[0011] In one or more embodiments, in the winding structure, along the reverse direction of the winding direction, the first section includes a starting section that exceeds the winding starting end of the positive electrode current collector, and along the thickness direction of the negative electrode sheet, both surfaces of the starting section are provided with a first negative electrode material layer. Through the above arrangement, while taking into account a high charging speed and good coulomb efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, it is beneficial to reduce the actual production cost and improve the production efficiency.
[0012] In one or more embodiments, the carbon material includes at least one of carbon nanotubes, graphene, carbon fiber, carbon black or pyrolytic carbon, the oxide includes at least one of silicon dioxide, aluminum oxide, titanium oxide or zinc oxide, and the polymer includes at least one of polyacrylonitrile, polyaniline, polypyrrole, polyvinyl alcohol or polyimide. By selecting the above different types of coating materials, it is beneficial to improve the stability of the lithium embedded area structure of the negative electrode plate, thereby improving the charging speed and coulomb efficiency of the secondary battery.
[0013] In one or more embodiments, the average thickness of the coating layer is 10 nm to 100 nm. By regulating the average thickness h of the coating layer within the above range, it is beneficial to increase the interlayer spacing between the negative electrode active materials, increase the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, thereby improving the stability of the structure of the lithium embedded area of the negative electrode plate, thereby improving the charging speed and coulomb efficiency of the secondary battery.
[0014] In one or more embodiments, the average particle size of the first negative electrode active material is D1 μm, the average particle size of the second negative electrode active material is D2 μm, and D1>D2. Through the above configuration, when the non-lithium insertion region uses the first negative electrode active material with a larger average particle size as the negative electrode active material, the compaction density of the non-lithium insertion region is relatively high, which reduces the risk of graphite exfoliation in the non-lithium insertion region caused by solvent co-intercalation in the non-lithium insertion region of the lithium-ion battery, and is conducive to further improving the cycle stability of the secondary battery.
[0015] In one or more embodiments, 10≤D1≤30, 5≤D2≤20. By regulating the values of D1 and D2 within the above range, the first negative electrode active material and the second negative electrode active material are used in combination, which is beneficial to reduce the risk of graphite exfoliation in the non-lithium intercalation region caused by solvent co-intercalation in the non-lithium intercalation region of the lithium ion battery while taking into account a higher charging speed and good coulombic efficiency, thereby improving the cycle performance of the secondary battery.
[0016] In one or more embodiments, the thickness of the first negative electrode material layer is H1 μm, the thickness of the second negative electrode material layer is H2 μm, 20%≤H1 / H2×100%≤60%, 120≤H2≤140. By regulating the values of H1 / H2×100% and H2 within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0017] In one or more embodiments, the compaction density PD1 of the first negative electrode material layer is 0.93 g / cm 3 Up to 3.79g / cm 3The compaction density PD2 of the second negative electrode material layer is 0.56 g / cm 3 Up to 0.76g / cm 3 By regulating the compaction density PD1 of the first negative electrode material layer and the compaction density PD2 of the second negative electrode material layer within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0018] In one or more embodiments, the unit coating weight CW1 of the first negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 The unit coating weight CW2 of the second negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 By regulating the unit coating weight CW1 of the first negative electrode material layer and the unit coating weight CW2 of the second negative electrode material layer within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0019] In one or more embodiments, the secondary battery further includes an electrolyte, the electrolyte includes an additive, and the additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) or lithium bis(fluorosulfonyl)imide (LiFSI). Based on the mass of the electrolyte, the mass percentage of the additive is 2% to 5%. By selecting the above-mentioned types of additives and regulating the content of the additives within the above-mentioned range, the electrolyte and the negative electrode plate work synergistically to improve the charging speed and coulomb efficiency of the secondary battery; at the same time, the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery is reduced, thereby improving the cycle performance of the secondary battery.
[0020] The second aspect of the present application provides an electronic device, comprising the secondary battery in any one of the above embodiments. Therefore, the electronic device of the present application has good performance.
[0021] Beneficial effects of the embodiments of the present application:
[0022] The embodiments of the present application provide a secondary battery and an electronic device. By coating different types of negative electrode active materials on the negative electrode plate in the lithium-ion battery in different areas, it is possible to achieve both fast charging performance and high coulombic efficiency in the lithium-ion battery's lithium-intercalation area, while reducing the risk of graphite exfoliation caused by solvent co-intercalation in the non-lithium-intercalation area of the lithium-ion battery.
[0023] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.
[0025] Figure 1 A schematic diagram of a winding structure formed by an electrode assembly in one embodiment of the present application;
[0026] Figure 2 A schematic diagram of a wound structure formed by an electrode assembly in another embodiment of the present application.
[0027] Reference numerals: electrode assembly 001 ; positive electrode plate 10 ; positive electrode current collector 11 ; positive electrode material layer 12 ; negative electrode plate 20 ; negative electrode current collector 21 ; first negative electrode material layer 22 ; second negative electrode material layer 23 ; separator 30 . DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0029] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0030] When fast-charging graphite with a coating layer is used to replace traditional graphite as the negative electrode active material in lithium-ion batteries, the fast-charging graphite can effectively reduce the direct contact between graphite and the electrolyte by forming a protective film on the surface of the graphite particles, reduce the occurrence of side reactions during the cycle, and thus improve the charging efficiency, kinetic performance and cycle life of the secondary battery. In the prior art, in lithium-ion batteries with fast-charging graphite as the negative electrode active material, when the structure of the electrode assembly is a winding type, it is usually required that the negative electrode material layer can cover the positive electrode material layer to prevent the generation of lithium precipitation, and the negative electrode plate is generally double-sided coated at the beginning and end sections beyond the positive electrode plate, which reduces the risk of powder loss and improves processing efficiency. However, when fast-charging graphite with a coating layer is used as the negative electrode active material and is used with an electrolyte that does not contain 1,3-propane sultone (PS), for electrode assemblies with multi-electrode ear structures, the film quality is poor in the non-lithium-embedded area at the head and tail of the pole piece, that is, the area of the negative pole piece without the positive pole piece (that is, the area where the negative electrode material layer is not opposite to the positive electrode material layer). At low temperatures (temperature ≤ 10°C), the desolvation ability of lithium ions is poor, and solvent co-embedding is prone to occur during charging and discharging, that is, solvent molecules are embedded in carbon materials such as graphite together with lithium ions to form a ternary graphite intercalation compound (t-GIC). At the same time, fast-charging graphite has a larger interlayer spacing, more micropores or a more uniform particle size distribution in its microstructure compared to ordinary graphite, and these structural features may aggravate the embedding of solvent molecules. This co-embedding mechanism not only affects the performance of lithium-ion batteries, such as capacity and cycle stability, but also affects the safety and service life of lithium-ion batteries. When the solvent co-intercalation is serious, graphite exfoliation will occur, resulting in convex spots on the appearance of the electrode assembly, which destroys the structural integrity of the negative electrode material layer. Based on this, the present application provides a secondary battery and an electronic device that can effectively improve the problem of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account the high charging speed and good coulomb efficiency of the secondary battery. The specific technical solution is as follows:
[0031] The first aspect of the present application provides a secondary battery, the secondary battery includes an electrode assembly of a winding structure, the electrode assembly includes a positive electrode sheet and a negative electrode sheet, in the winding structure, along the opposite direction of the winding direction of the electrode assembly, the winding start end of the negative electrode sheet exceeds the winding start end of the positive electrode sheet. The positive electrode sheet includes a positive electrode collector, the negative electrode sheet includes a negative electrode collector, along the length direction of the unfolded negative electrode sheet, and along the winding direction of the electrode assembly, the negative electrode collector includes a first section and a second section connected in sequence, in the winding structure, the first section is a portion of at least one surface of the negative electrode collector that is not opposite to the positive electrode collector, and the second section is a portion of both surfaces of the negative electrode collector that are opposite to the positive electrode collector. Wherein, the negative electrode sheet includes a first negative electrode material layer and a second negative electrode material layer arranged on the surface of the negative electrode collector, the first negative electrode material layer includes a first negative electrode active material, and the first negative electrode active material includes at least one of artificial graphite or natural graphite. The second negative electrode material layer includes a second negative electrode active material, the second negative electrode active material includes at least one of artificial graphite or natural graphite with a coating layer, the coating layer includes a coating material, and the coating material includes one of a carbon material, an oxide or a polymer. The first section is provided with the first negative electrode material layer on at least a portion of the surface facing the winding center of the electrode assembly, and the second section is provided with the second negative electrode material layer on at least a portion of the surface facing the winding center of the electrode assembly.
[0032] The winding direction of the electrode assembly is defined as the W direction. Figure 1 As shown, the electrode assembly 001 includes a positive electrode sheet 10, a negative electrode sheet 20 and a separator 30. Along the opposite direction of the winding direction (W direction) of the electrode assembly 001, the winding start end P of the negative electrode sheet 20 exceeds the winding start end O of the positive electrode sheet. The positive electrode sheet 10 includes a positive electrode collector 11, and the negative electrode sheet 20 includes a negative electrode collector 21. Along the length direction of the unfolded negative electrode sheet 20 and along the winding direction (W direction) of the electrode assembly 001, the negative electrode collector 21 includes a first section and a second section connected in sequence. The first section is a portion where at least one surface of the negative electrode collector 21 is not opposite to the positive electrode collector 11, and the second section is a portion where both surfaces of the negative electrode collector 21 are opposite to the positive electrode collector 11, that is, along the winding direction (W direction), the winding start end P of the negative electrode sheet 20 is wound at least one circle to the portion aligned with the winding start end O of the positive electrode sheet 10, that is, the first section is P to Q, and correspondingly, the second section is Q to M. Among them, the negative electrode plate 20 includes a first negative electrode material layer 22 and a second negative electrode material layer 23 arranged on the surface of the negative electrode collector 21. The first section is provided with the first negative electrode material layer 22 on the surface facing the winding center of the electrode assembly 001, and the second section is provided with the second negative electrode material layer 23 on the surface facing the winding center of the electrode assembly 001.
[0033] In the electrode assembly of the winding structure of the present application, the first section is the part where at least one surface of the negative electrode current collector is not opposite to the positive electrode current collector. When the secondary battery is charged and discharged, the negative electrode material layer on the surface of the first section facing the winding center of the electrode assembly has no lithium ions, so the negative electrode material layer on the surface of the first section facing the winding center of the electrode assembly is a non-lithium insertion area. The second section is the part where both surfaces of the negative electrode current collector are opposite to the positive electrode current collector. When the secondary battery is charged and discharged, the negative electrode material layer on both surfaces of the second section has lithium ion transmission, so the negative electrode material layer on both surfaces of the second section facing and away from the winding center of the electrode assembly is a lithium insertion area. The present application applies different negative electrode active materials on the negative electrode plate in a zone-by-zone manner, that is, different negative electrode active materials are selected in the lithium insertion area and non-lithium insertion area of the negative electrode plate, and the lithium insertion area uses artificial graphite and / or natural graphite with a coating layer as the negative electrode active material, which can increase the interlayer spacing, improve the diffusion rate of lithium ions, and form a stable solid electrolyte interface (SEI) film on the surface of the negative electrode plate, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, thereby improving the charging speed and coulomb efficiency of the secondary battery; the non-lithium insertion area uses artificial graphite and / or natural graphite as the negative electrode active material, and the conventional graphite material has a small interlayer spacing and fewer micropores in the microstructure, which is conducive to reducing the embedding of solvent molecules during the charging and discharging process, thereby reducing the risk of graphite exfoliation in the non-lithium insertion area caused by solvent co-embedding in the non-lithium insertion area of the lithium ion battery. Therefore, the secondary battery of the present application can effectively reduce the risk of graphite exfoliation in the non-lithium insertion area caused by solvent co-embedding in the non-lithium insertion area of the lithium ion battery while taking into account a high charging speed and good coulomb efficiency.
[0034] In the present application, the coating layer is completely coated on the surface of the graphite material (i.e., artificial graphite and / or natural graphite) particles. The above "complete coating" is at least partially homogeneous layer coating, that is, at least part of the coating layer is uniformly coated on the surface of the graphite material particles with uniform thickness.
[0035] In one or more embodiments, at least a portion of the surface of the first section facing away from the winding center of the electrode assembly is provided with a second negative electrode material layer, the positive electrode sheet includes a positive electrode material layer, and the surface of the positive electrode current collector opposite to the second negative electrode material layer is provided with a positive electrode material layer. Figure 1As shown, the first section is from P to Q, and the surface of the first section away from the winding center of the electrode assembly 001 is entirely provided with a second negative electrode material layer 23, the positive electrode plate 10 includes a positive electrode material layer 12, and the surface of the positive electrode collector 11 opposite to the second negative electrode material layer 23 is provided with a positive electrode material layer 12. Through the above arrangement, the second negative electrode material layer is opposite to the positive electrode material layer, which is beneficial to increase the interlayer spacing and the diffusion rate of lithium ions during the charge and discharge process of the secondary battery, and form a stable SEI film on the surface of the negative electrode plate, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, while reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, it is beneficial to improve the charging speed and coulomb efficiency of the secondary battery.
[0036] In one or more embodiments, the width of the electrode assembly is L mm, and along the length direction of the unfolded negative electrode sheet, the length of the first section is L1 mm, 1.5≤L1 / L≤2.5, 39.0≤L≤40.5. For example, the value of L1 / L can be 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, or a range consisting of any two of them; the value of L can be 39.0, 39.1, 39.2, 39.4, 39.5, 39.6, 39.7, 39.8, 39.9, 40, 40.1, 40.2, 40.3, 40.4, 40.5, or a range consisting of any two of them. By regulating the values of L1 / L and L within the above range, different negative electrode active materials are coated on the negative electrode plate in different regions. While taking into account a high charging speed and good coulombic efficiency, it is beneficial to reduce the embedding of solvent molecules during the charging and discharging process, thereby reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, and at the same time, it is beneficial to reduce the risk of the non-lithium intercalation area of the first segment being too long, thereby reducing the energy density and kinetic performance of the secondary battery.
[0037] In one or more embodiments, 58.5≤L1≤101.25. For example, the value of L1 can be 58.5, 60, 70, 80, 90, 100, 101, 101.25 or a range consisting of any two of these values. By regulating the value of L1 within the above range, different negative electrode active materials are coated on the negative electrode plate in a zone-by-zone manner, which helps to reduce the embedding of solvent molecules during the charge and discharge process while taking into account a higher charging speed and good coulombic efficiency, thereby reducing the risk of graphite exfoliation in the non-lithium intercalation zone caused by co-embedding of solvent in the non-lithium intercalation zone in the lithium-ion battery, and at the same time helps to reduce the risk of the non-lithium intercalation zone in the first segment being too long, thereby reducing the energy density and kinetic performance of the secondary battery.
[0038] In one or more embodiments, the negative electrode current collector further includes a third section connected to the second section, along the winding direction of the electrode assembly, the third section is a portion of at least one surface of the negative electrode current collector that is not opposite to the positive electrode current collector, at least a portion of the surface of the third section away from the winding center of the electrode assembly is provided with a first negative electrode material layer, and at least a portion of the surface of the third section facing the winding center of the electrode assembly is provided with a second negative electrode material layer. For example, Figure 1 and Figure 2 As shown, the negative electrode current collector 21 also includes a third section connected to the second section, that is, in the opposite direction of the winding direction (W direction), the winding end N of the negative electrode sheet 20 is wound at least one circle to the part aligned with the winding end O' of the positive electrode sheet 10, that is, along the winding direction (W direction), the second section is Q to M, the third section is M to N, and the surface of the third section away from the winding center of the electrode assembly 001 is provided with a first negative electrode material layer 22, and the surface of the third section facing the winding center of the electrode assembly 001 is provided with a second negative electrode material layer 23. In the electrode assembly of the winding structure of the present application, when the secondary battery is charged and discharged, the negative electrode material layer on the surface of the third section away from the winding center of the electrode assembly has no lithium ions, so the negative electrode material layer on the surface of the third section away from the winding center of the electrode assembly is a non-lithium insertion area. The negative electrode material layer on the surface of the third section facing the winding center of the electrode assembly is opposite to the positive electrode material layer. There is lithium ion transmission when the secondary battery is charged and discharged, so the negative electrode material layer on the surface of the third section facing the winding center of the electrode assembly is a lithium insertion area. Through the above-mentioned setting, the lithium insertion area at the end of the negative electrode plate uses artificial graphite and / or natural graphite with a coating layer as the negative electrode active material, which is conducive to increasing the interlayer spacing, improving the diffusion rate of lithium ions, and forming a stable SEI film on the surface of the negative electrode plate, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, thereby improving the charging speed and coulomb efficiency of the secondary battery; the non-lithium insertion area at the end of the negative electrode plate uses conventional graphite material as the negative electrode active material, which is conducive to reducing the embedding of solvent molecules during the charging and discharging process, thereby further reducing the risk of graphite exfoliation in the non-lithium insertion area caused by the co-embedding of solvent in the non-lithium insertion area in the lithium ion battery. Therefore, the secondary battery is conducive to further reducing the risk of graphite exfoliation in the non-lithium insertion area caused by the co-embedding of solvent in the non-lithium insertion area in the lithium ion battery while taking into account a higher charging speed and good coulomb efficiency.
[0039] In one or more embodiments, the width of the electrode assembly is L mm, and along the length direction of the unfolded negative electrode sheet, the length of the third section is L2 mm, 1.5≤L2 / L≤3.0, 39.0≤L≤40.5. For example, the value of L2 / L can be 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or any two thereof; the value of L can be 39, 39.5, 39.6, 39.7, 39.8, 39.9, 40, 40.1, 40.2, 40.3, 40.4, 40.5 or a range consisting of any two thereof. For example, Figure 1 As shown, the width of the electrode assembly 001 is L mm. By adjusting the values of L2 / L and L within the above range, different negative electrode active materials are coated on the negative electrode sheet in a zone-by-zone manner, which is conducive to reducing the embedding of solvent molecules during the charging and discharging process while taking into account a high charging speed and good coulombic efficiency, thereby reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-embedding in the non-lithium intercalation area of the lithium-ion battery, and at the same time, it is conducive to reducing the risk of the non-lithium intercalation area of the third segment being too long, which reduces the energy density and kinetic performance of the secondary battery.
[0040] In one or more embodiments, 58.5≤L2≤121.5. For example, the value of L2 can be 58.5, 59, 60, 70, 80, 90, 100, 110, 120, 121, 121.5 or a range consisting of any two of these values. By regulating the value of L2 within the above range, different negative electrode active materials are coated on the negative electrode plate in a zone-by-zone manner, which helps to reduce the embedding of solvent molecules during the charging and discharging process while taking into account a higher charging speed and good coulombic efficiency, thereby reducing the risk of graphite exfoliation in the non-lithium intercalation zone caused by co-embedding of solvent in the non-lithium intercalation zone in the lithium-ion battery, and at the same time helps to reduce the risk of the non-lithium intercalation zone of the third segment being too long, thereby reducing the energy density and kinetic performance of the secondary battery.
[0041] In one or more embodiments, in the winding structure, in the reverse direction of the winding direction, the first section includes a starting section that exceeds the winding starting end of the positive electrode collector, and along the thickness direction of the negative electrode sheet, both surfaces of the starting section are provided with the first negative electrode material layer. For example, Figure 2As shown, in the electrode assembly 001 of the winding structure, along the reverse direction of the winding direction (W direction), the first section is P to Q, the first section includes the starting section beyond the winding starting end O of the positive electrode current collector 11, along the winding direction (W direction), the starting section is P to P', and along the thickness direction of the negative electrode sheet 20, the first negative electrode material layer 22 is provided on both surfaces of the starting section. Through the above arrangement, while taking into account a high charging speed and good coulomb efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, it is conducive to reducing the actual production cost and improving the production efficiency.
[0042] In one or more embodiments, in the winding structure, along the winding direction, the third section includes a tail section that exceeds the winding tail end of the positive electrode collector. Along the thickness direction of the negative electrode sheet, both surfaces of the tail section are provided with the first negative electrode material layer. For example, Figure 2 As shown, in the electrode assembly 001 of the winding structure, along the winding direction (W direction), the third section is M to N, the third section includes a tail section that exceeds the winding tail end O' of the positive electrode collector 11, and the tail end is N' to N, and along the thickness direction of the negative electrode sheet 20, a first negative electrode material layer 22 is provided on both surfaces of the tail section. Through the above arrangement, while taking into account a high charging speed and good coulomb efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, it is conducive to reducing the actual production cost and improving the production efficiency.
[0043] In one or more embodiments, the carbon material includes at least one of carbon nanotubes, graphene, carbon fiber, carbon black or pyrolytic carbon, the oxide includes at least one of silicon dioxide, aluminum oxide, titanium oxide or zinc oxide, and the polymer includes at least one of polyacrylonitrile, polyaniline, polypyrrole, polyvinyl alcohol or polyimide. By selecting the above-mentioned different types of coating materials, it is beneficial to increase the interlayer spacing between the negative electrode active materials, increase the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, reduce the occurrence of side reactions between the negative electrode active materials and the electrolyte, and improve the stability of the structure of the lithium embedded area of the negative electrode plate, thereby improving the charging speed and coulomb efficiency of the secondary battery.
[0044] In one or more embodiments, the average thickness h of the coating layer is 10nm to 100nm. For example, the thickness h of the coating layer can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 10nm or a range consisting of any two of the values. By regulating the average thickness h of the coating layer within the above range, it is beneficial to increase the interlayer spacing between the negative electrode active materials, increase the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, reduce the occurrence of side reactions between the negative electrode active materials and the electrolyte, and improve the stability of the structure of the lithium embedded area of the negative electrode plate, thereby improving the charging speed and coulomb efficiency of the secondary battery. The present application has no particular restrictions on the method for regulating the average thickness h of the coating layer, as long as the purpose of the present application can be achieved. For example, the "coating layer thickness test", "coating layer mass percentage test" and "fast-filling graphite performance test" in the present application can be combined to select commercially available fast-filling graphite with different coating layer thicknesses.
[0045] In one or more embodiments, the average particle size of the first negative electrode active material is D1 μm, the average particle size of the second negative electrode active material is D2 μm, and D1>D2. Through the above configuration, when the non-lithium insertion region uses the first negative electrode active material with a larger average particle size as the negative electrode active material, the compaction density of the non-lithium insertion region is relatively high, which reduces the risk of graphite exfoliation in the non-lithium insertion region caused by solvent co-intercalation in the non-lithium insertion region of the lithium-ion battery, and is conducive to further improving the cycle stability of the secondary battery.
[0046] In one or more embodiments, 10≤D1≤30, 5≤D2≤20. For example, the value of D1 can be 10, 12, 15, 18, 20, 22, 25, 28, 30, or a range consisting of any two of the values; the value of D2 can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or a range consisting of any two of the values. By regulating the values of D1 and D2 within the above range, the average particle size of the second negative electrode active material is smaller, which is conducive to improving the diffusion rate of lithium ions, and forming a stable SEI film on the surface of the negative electrode sheet, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, thereby improving the charging speed and coulomb efficiency of the secondary battery; the average particle size of the first negative electrode active material is larger, and the compaction density is larger at this time, which is conducive to improving the volume energy density of the secondary battery. The use of the first negative electrode active material and the second negative electrode active material in combination is beneficial to reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by co-intercalation of solvent in the non-lithium intercalation area of the lithium-ion battery while taking into account a high charging speed and good coulombic efficiency, and improve the cycle performance of the secondary battery. The present application has no special restrictions on the regulation method of the average particle size D1 of the first negative electrode active material and the average particle size D2 of the second negative electrode active material, as long as the purpose of the present application can be achieved. For example, the average particle size of the first negative electrode active material and the second negative electrode active material can be regulated by grading and grinding the particles of the first negative electrode active material and the second negative electrode active material. Exemplarily, when other conditions remain unchanged, the grinding time of the first negative electrode active material particles is extended, and the average particle size D1 of the first negative electrode active material is reduced; the grinding time of the first negative electrode active material particles is shortened, and the average particle size D1 of the first negative electrode active material is increased.
[0047] In one or more embodiments, the thickness of the first negative electrode material layer is H1 μm, the thickness of the second negative electrode material layer is H2 μm, 20%≤H1 / H2×100%≤60%, 120≤H2≤140. For example, the value of H1 / H2×100% can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of the values; the value of H2 can be 120, 122, 125, 128, 130, 132, 135, 138, 140 or a range consisting of any two of the values. By regulating the values of H1 / H2×100% and H2 within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0048] In one or more embodiments, 24≤H1≤84. For example, the value of H1 can be 24, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65, 68, 70, 72, 75, 78, 80, 82, 84 or a range consisting of any two of the values. By regulating the value of H1 within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0049] In one or more embodiments, the compaction density PD1 of the first negative electrode material layer is 0.93 g / cm 3 Up to 3.79g / cm 3 The compaction density PD2 of the second negative electrode material layer is 0.56 g / cm 3 Up to 0.76g / cm 3 For example, the compaction density PD1 of the first negative electrode material layer may be 0.93 g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 , 1g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 , 2g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 , 3g / cm 3 、3.2g / cm 3 , 3.5g / cm 3 、3.7g / cm 3 、3.75g / cm 3 、3.79g / cm 3 or a range consisting of any two values thereof; the compaction density PD2 of the second negative electrode material layer may be 0.56 g / cm 3 、0.58g / cm 3 , 0.6g / cm 3 , 0.62g / cm 3 , 0.65g / cm 3 , 0.68g / cm 3 , 0.7g / cm 3 , 0.72g / cm 3 , 0.75g / cm 3 , 0.76g / cm3 Or a range consisting of any two of the values. By regulating the compaction density PD1 of the first negative electrode material layer and the compaction density PD2 of the second negative electrode material layer within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0050] In one or more embodiments, the unit coating weight CW1 of the first negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 The unit coating weight CW2 of the second negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 For example, the unit coating weight CW1 of the first negative electrode material layer may be 120 mg / 1540.25 mm 2 、122mg / 1540.25mm 2 、125mg / 1540.25mm 2 、128mg / 1540.25mm 2 、130mg / 1540.25mm 2 、132mg / 1540.25mm 2 、135mg / 1540.25mm 2 、138mg / 1540.25mm 2 、140mg / 1540.25mm 2 or a range consisting of any two values thereof; the unit coating weight CW2 of the second negative electrode material layer may be 120 mg / 1540.25 mm 2 、122mg / 1540.25mm 2 、125mg / 1540.25mm 2 、128mg / 1540.25mm 2 、130mg / 1540.25mm 2 、132mg / 1540.25mm 2 、135mg / 1540.25mm 2 、138mg / 1540.25mm 2 、140mg / 1540.25mm 2Or a range consisting of any two of the values. By regulating the unit coating weight CW1 of the first negative electrode material layer and the unit coating weight CW2 of the second negative electrode material layer within the above range, while taking into account a higher charging speed and good coulombic efficiency, reducing the risk of graphite stripping in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery, the negative electrode sheet has a higher capacity, and while taking into account the actual production cost, the secondary battery has a higher energy density.
[0051] In one or more embodiments, within the range of 0 to 2.0 V, the actual gram capacity of the first negative electrode active material and / or the second negative electrode active material is ≥300 mAh / g. Through the above configuration, the fast charging capability of the fast-charging graphite is ensured, the lithium ion diffusion rate is improved, and the secondary battery has a high Coulomb efficiency, while also improving the graphite exfoliation problem caused by the co-intercalation of solvents in the non-lithium intercalation area.
[0052] In one or more embodiments, based on the mass of the second negative electrode active material, the mass percentage of the coating layer is 5% to 15%. For example, the mass percentage of the coating layer can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, or a range consisting of any two of these values. By regulating the mass percentage of the coating layer within the above range, it is beneficial to increase the interlayer spacing between the negative electrode active materials, increase the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, reduce the occurrence of side reactions between the negative electrode active materials and the electrolyte, and improve the stability of the structure of the lithium embedded area of the negative electrode plate, thereby improving the charging speed and coulomb efficiency of the secondary battery.
[0053] In one or more embodiments, artificial graphite and / or natural graphite with a coating layer is used as a negative electrode active material to assemble a button battery, the button battery is charged to 4.35V at a constant current of 2C, then charged to 0.05C at a constant voltage of 4.35V, and discharged to 2.4V at a constant current of 0.5C, this is one charge and discharge cycle, and the cycle capacity retention rate of the button battery after 10 charge and discharge cycles is ≥80%. At this time, the artificial graphite and / or natural graphite of the coating layer is used as the second negative electrode active material in the secondary battery, and the secondary battery has good fast charging performance.
[0054] The present application has no particular restrictions on the preparation method of the second negative electrode active material, as long as the purpose of the present application can be achieved. For example, the commercially available negative electrode active material required for the present application can be selected in combination with the "test of the thickness of the coating layer", "test of the mass percentage of the coating layer" and "test of the performance of fast-charging graphite" in the present application.
[0055] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector. For example, the composite current collector can be a lithium copper composite current collector, a carbon copper composite current collector, a nickel copper composite current collector, a titanium copper composite current collector, etc. In the present application, the first negative electrode material layer and the second negative electrode material layer may also include a conductive agent and a negative electrode binder. The present application has no particular restrictions on the type of conductive agent in the first negative electrode material layer and the second negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the type of negative electrode binder in the first negative electrode material layer and the second negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. Optionally, the first negative electrode material layer and the second negative electrode material layer also include a thickener. The present application has no particular restrictions on the type of thickener, as long as the purpose of the present application can be achieved. For example, the thickener may include at least one of carboxymethyl cellulose or sodium carboxymethyl cellulose. The present application does not specifically limit the mass ratio of the first negative electrode active material, the conductive agent, the negative electrode binder and the thickener in the first negative electrode material layer, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. The present application does not specifically limit the mass ratio of the second negative electrode active material, the conductive agent, the negative electrode binder and the thickener in the second negative electrode material layer, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved.
[0056] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular restrictions on the type of positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05 O2 (NCM955), NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate or lithium iron manganese phosphate. In the present application, the positive electrode active material may also contain non-metallic elements, for example, the non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. In the present application, the positive electrode material layer may also include a positive electrode binder and a conductive agent. The present application does not particularly limit the type of the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may be the same as the type of the negative electrode binder in the above-mentioned negative electrode material layer. The present application does not particularly limit the type of the conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be the same as the type of the conductive agent in the above-mentioned negative electrode material layer. The present application has no particular restriction on the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0057] The present application does not have any special restrictions on the preparation method of the negative electrode sheet, as long as it can achieve the purpose of the present application. For example, the preparation method of the negative electrode sheet may include but is not limited to the following steps: (1) pre-winding the negative electrode collector and the prepared positive electrode sheet, determining the surface of the negative electrode collector facing the electrode assembly, the surface away from the electrode assembly, and the first section, the second section, and the third section; (2) preparing the first negative electrode slurry and the second negative electrode slurry; (3) coating the first negative electrode slurry or the second negative electrode slurry on different sections of the surface of the negative electrode collector facing the electrode assembly according to the setting, and drying to obtain a single-sided coated negative electrode sheet; (4) coating the first negative electrode slurry or the second negative electrode slurry on different sections of the surface of the negative electrode collector away from the electrode assembly according to the setting, and drying to obtain a double-sided coated negative electrode sheet; (5) cold pressing and cutting to obtain the negative electrode sheet.
[0058] The present application has no particular restrictions on the solid content of the first negative electrode slurry and the second negative electrode slurry, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the process parameters of the above-mentioned drying, cold pressing, cutting, and striping, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0059] In one or more embodiments, the secondary battery further comprises an electrolyte, the electrolyte comprises an additive, the additive comprises at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) or lithium bis(fluorosulfonyl)imide (LiFSI), and the mass percentage of the additive is 2% to 5% based on the mass of the electrolyte. For example, the mass percentage of the additive may be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two of the values. By selecting the above-mentioned types of additives and regulating the content of the additives within the above-mentioned range, the electrolyte and the negative electrode plate synergistically act to improve the diffusion rate of lithium ions, and form a stable SEI film on the surface of the negative electrode plate, reducing the occurrence of side reactions between the negative electrode active material and the electrolyte, thereby improving the charging speed and coulomb efficiency of the secondary battery; at the same time, the risk of graphite exfoliation in the non-lithium intercalation zone caused by the co-intercalation of solvents in the non-lithium intercalation zone of the lithium ion battery is reduced, and the cycle performance of the secondary battery is improved.
[0060] In the present application, the electrolyte includes lithium salts and non-aqueous solvents in addition to additives. The present application has no special restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiFSI, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no special restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no special restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compound may include but is not limited to at least one of diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC) or methylethyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to butylene carbonate (BC). The fluorinated carbonate compound may include but is not limited to at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methylcyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0061] In the present application, the electrode assembly also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane. In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven membrane or a composite membrane having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene). In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0062] The secondary battery also includes a shell for accommodating the first pole piece, the diaphragm, the second pole piece and the electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0063] The preparation process of the secondary battery of the present application is well known to those skilled in the art and is not particularly limited in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the first electrode sheet, the separator and the second electrode sheet in sequence, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery.
[0064] The second aspect of the present application provides an electronic device, comprising the secondary battery in any one of the above embodiments. Therefore, the electronic device of the present application has good performance.
[0065] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0066] Example
[0067] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0068] Test methods and equipment:
[0069] Test of coating thickness:
[0070] The artificial graphite and / or natural graphite with a coating layer (i.e., the second negative electrode active material) was sliced using a focused ion beam (FIB), and then characterized by a high-resolution transmission electron microscope (HRTEM, model Talos F200X). Within the same selection range (500,000 times magnification), five positions of the coating layer were randomly selected to measure the thickness of the coating layer in the particles of the second negative electrode active material. The arithmetic mean of the thickness of the coating layer at the five different positions was calculated to obtain the average thickness h of the coating layer.
[0071] Test of mass percentage of coating layer:
[0072] The artificial graphite and / or natural graphite with coating layer was scanned by laser microconfocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instruments Division) with a test range of 100 cm -1 Up to 4000cm -1 ; and use LabSpec software to process the data and analyze and confirm the type of coating material in the coating layer.
[0073] The artificial graphite and / or natural graphite with coating layer is tested by thermogravimetric analyzer (model: STA499C), wherein the mass loss ratio of the tested sample at 1000°C is the mass percentage of the coating layer.
[0074] Fast-filling graphite performance test:
[0075] Artificial graphite and / or natural graphite with a coating layer, binder styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 85℃ to obtain a negative electrode sheet; the negative electrode sheet was cut into a disc with a diameter of 14mm and used as a working electrode, a metal lithium sheet was used as a counter electrode, and a polyethylene (PE) film with a thickness of 7μm was used as a separator, and a button cell was assembled after injecting the test electrolyte. The button cell was charged and discharged. At an ambient temperature of 25°C, the button cell was charged to 4.35V at 2C constant current, then charged to 0.05C at 4.35V constant voltage, and discharged to 2.4V at 0.5C constant current, and left to stand for 30 minutes. The discharge capacity of the first cycle was recorded, and then 10 charge and discharge cycles were performed, and the discharge capacity of the 10th cycle was recorded. The cycle capacity retention rate of the button cell after 10 cycles was recorded and calculated.
[0076] Cycle capacity retention rate (%) = (discharge capacity at the 10th cycle / discharge capacity at the first cycle) × 100%.
[0077] When the calculated cycle capacity retention rate is ≥80%, the artificial graphite and / or natural graphite with a coating layer can be used as fast-charging graphite and applied to secondary batteries, and the secondary batteries have good fast-charging performance.
[0078] Tests for L1, L2, L, H1, H2, D1, D2:
[0079] At an ambient temperature of 25°C, the lithium-ion battery was disassembled to obtain an electrode assembly with a wound structure, and the width L of the electrode assembly was measured with a soft ruler. According to the starting position of the positive and negative electrode sheets and the relative relationship between the positive and negative electrode sheet material layers, the positions of the first, second and third sections of the negative electrode collector were determined. The negative electrode sheet was taken out and soaked in dimethyl carbonate (DMC) for 20 minutes, then placed in an oven and dried at 80°C for 12 hours to obtain a test sample of the negative electrode sheet.
[0080] The negative electrode sheet is unfolded, and the length L1 of the first section and the length L2 of the third section of the negative electrode current collector after unfolding are measured with a soft ruler. The cross section of the negative electrode sheet along the thickness direction of the negative electrode sheet and the length direction after unfolding is prepared, and the cross section is ion polished and observed with a scanning electron microscope. According to the position and orientation of the first section, the second section and the third section, the first negative electrode material layer and the second negative electrode material layer are determined, and the thickness H1 of the first negative electrode material layer and the thickness H2 of the second negative electrode material layer are measured respectively. The cross sections of the first negative electrode material layer and the second negative electrode material layer are observed, and 10 particles of the first negative electrode active material and 10 particles of the second negative electrode active material are randomly selected, and the equivalent diameters of the 10 particles of the first negative electrode active material and the 10 particles of the second negative electrode active material are measured respectively (that is, the diameter of a circle of equal area converted from a particle with an irregular cross section), and the average values are calculated to obtain the average particle size D1 of the first negative electrode active material and the average particle size D2 of the second negative electrode active material.
[0081] CW1, CW2 test:
[0082] At an ambient temperature of 25°C, the lithium-ion battery was disassembled to obtain an electrode assembly of a wound structure. The positions and orientations of the first, second, and third sections of the negative electrode current collector were determined according to the starting positions of the positive and negative electrode sheets and the relative relationship between the positive and negative electrode sheet material layers. The negative electrode sheet was taken out and soaked in dimethyl carbonate (DMC) for 20 minutes, then placed in an oven and dried at 80°C for 12 hours to obtain a test sample of the negative electrode sheet.
[0083] The negative electrode sheet sample was punched and broken into two small discs with a radius of 22.14 mm (area of 1540.25 mm) at the first section of the negative electrode current collector. 2 ), weigh them one by one and take the average value, which is recorded as a; wipe the negative electrode material layer on the surface of the small disc away from the winding center of the electrode assembly with deionized water, weigh them one by one and take the average value, which is recorded as a1. The negative electrode sheet sample is punched and broken into 4 small discs with a radius of 22.14mm (area of 1540.25mm) at the position of the second section of the negative current collector. 2), weigh them one by one and take the average value, which is recorded as b; use deionized water to wipe the negative electrode material layer on the surface of the small disc away from the winding center of the electrode assembly, weigh them one by one and take the average value, which is recorded as b1, then,
[0084] Unit coating weight of the first negative electrode material layer CW1=(a-a1) / 1540.25;
[0085] The unit coating weight of the second negative electrode material layer CW2=(b-b1) / 1540.25.
[0086] PD1 and PD2 tests:
[0087] Refer to the "CW1, CW2 test" to obtain the unit coating weight CW1 of the first negative electrode material layer and the unit coating weight CW2 of the second negative electrode material layer, and refer to the "L1, L2, L, H1, H2, D1, D2 test" to obtain the thickness H1 of the first negative electrode material layer and the thickness H2 of the second negative electrode material layer, then calculate PD1 and PD2 according to the following formula:
[0088] Compacted density of the first negative electrode material layer=unit coating weight of the first negative electrode material layer / thickness of the first negative electrode material layer;
[0089] The compaction density of the second negative electrode material layer=the unit coating weight of the second negative electrode material layer / the thickness of the second negative electrode material layer.
[0090] Low temperature cycle demoulding test:
[0091] The test temperature was maintained at 0°C, and the lithium-ion batteries in the examples and comparative examples were charged to 4.25V at a constant current of 0.1C, then charged to a current of ≤0.05C at a constant voltage of 4.25V, left to stand for 30 minutes, and discharged to 2.4V at a constant current of 0.5C, left to stand for 30 minutes. The above steps were recorded as one cycle, and each group of lithium-ion batteries was cycled 10 times. After the cycle was completed, each group of lithium-ion batteries was disassembled, the negative electrode plates were taken out, and the states of the negative electrode material layers in different regions on each group of negative electrode plates were observed and recorded.
[0092] The demolding state of the non-lithium intercalation area in the lithium-ion battery is determined based on the demolding area ratio, wherein the demolding area ratio is calculated based on the total area of the material layer in the non-lithium intercalation area.
[0093] Coulomb efficiency test:
[0094] During the low-temperature cycle demoulding test of the lithium-ion batteries of each group of the above-mentioned embodiments and comparative examples, the charging capacity of the lithium-ion battery is recorded when the constant voltage charging is performed for the first cycle to a current of ≤0.05C, and then the discharge capacity of the lithium-ion battery is recorded when the constant current discharge is performed at 0.5C to 2.4V, and the percentage of the discharge capacity of the lithium-ion battery to the charging capacity in the first cycle is calculated. Then, the percentage of the discharge capacity of the lithium-ion battery to the charging capacity in each cycle is recorded and calculated. The average of the 10 percentages calculated is the coulombic efficiency of the lithium-ion battery group.
[0095] Charging speed test:
[0096] The test temperature is maintained at 0°C, and the lithium-ion batteries in the examples and comparative examples are charged to 4.25V at a constant current of 0.1C, then charged to a current of 0.05C at a constant voltage of 4.25V, left to stand for 30 minutes, and discharged to 2.4V at a constant current of 0.5C, left to stand for 30 minutes. The above steps are recorded as 1 cycle, and each group of lithium-ion batteries is cycled 10 times. After that, the lithium-ion battery is placed in an environment of 25°C, and then charged to 4.3V at a constant current of 0.5C, and charged to 0.05C at a constant voltage of 4.3V, left to stand for 15 minutes, and the lithium-ion battery is disassembled to observe the lithium deposition state on the surface of the lithium embedded area of the negative electrode plate. The non-lithium deposited area on the surface of the lithium embedded area of the negative electrode plate is golden yellow, and the lithium deposited area is off-white. The boundary value of the lithium deposition rate of the lithium embedded area of the negative electrode plate is based on the result of measuring the minimum lithium deposition rate.
[0097] If there is no lithium deposition on the surface of the lithium embedded area of the negative electrode, the lithium-ion battery prepared in the same way is charged and discharged at a test temperature of 0°C with a charge rate increased by 0.1C. The other charge and discharge parameters are the same as the above charge and discharge steps. After 10 cycles, the lithium-ion battery is placed in an environment of 25°C, and then charged to 4.3V at a constant current rate of 0.5C, and charged to 0.05C at a constant voltage of 4.3V. After standing for 15 minutes, the lithium-ion battery is disassembled to observe the lithium deposition state on the surface of the lithium embedded area of the negative electrode. The charge rate is increased by 0.1C each time until the lithium deposition in the lithium embedded area of the negative electrode ends the test, and the lithium deposition rate boundary value of the lithium embedded area of the negative electrode is recorded.
[0098] The charging speed of the lithium-ion battery is characterized by the lithium plating rate boundary value of the lithium-embedded area of the negative electrode plate, wherein the higher the lithium plating rate boundary value of the lithium-embedded area of the negative electrode plate, the faster the charging speed of the lithium-ion battery.
[0099] Example 1-1
[0100] <Preparation of positive electrode sheet>
[0101] The positive electrode active material lithium manganese iron phosphate (LMFP), the positive electrode binder polyvinylidene fluoride (PVDF) and the conductive carbon black are dispersed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 94.8:2.8:2.4, and the mixture is stirred thoroughly to obtain a positive electrode slurry with a solid content of 72wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 105°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. After that, the above steps are repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a double-sided positive electrode material layer. Then, after cold pressing, cutting and striping, it is dried under vacuum conditions at 105°C for 4h to obtain a positive electrode sheet with a specification of 1600mm×64mm for standby use. Among them, the coating weight of the positive electrode material layer is 280mg / 1540.25mm 2 The compaction density of the positive electrode material layer is 2.20g / cm 3 There are some empty foil areas of the positive electrode current collector with pole ears, and the specifications of the positive electrode current collector with a positive electrode material layer are 1600mm×64mm.
[0102] <Preparation of negative electrode sheet>
[0103] A copper foil with a thickness of 6 μm was selected as the negative electrode current collector. The negative electrode current collector and the prepared positive electrode sheet were pre-wound. The surface of the negative electrode current collector facing the pre-winding center, the surface away from the pre-winding center, and the first, second and third sections were determined. The length L1 of the first section was 80 mm, and the length of the third section accounted for L2 of 80 mm.
[0104] The first negative electrode active material artificial graphite, conductive carbon black (Super P), and styrene butadiene rubber (SBR) are mixed at a weight ratio of 97:1.5:1.5, deionized water is added as a solvent, and the mixture is stirred evenly to form a first negative electrode slurry with a solid content of 57wt%; the artificial graphite coated with carbon nanotubes is used as the second negative electrode active material, wherein the average thickness of the coating layer is 50nm; based on the mass of the second negative electrode active material, the mass percentage of the coating layer is 7%, and the cycle capacity retention rate of the button battery composed of artificial graphite coated with carbon nanotubes is 86%. The second negative electrode active material, conductive carbon black (Super P), and styrene butadiene rubber (SBR) are mixed at a weight ratio of 97:1.5:1.5, deionized water is added as a solvent, and the mixture is stirred evenly to form a second negative electrode slurry with a solid content of 57wt%. The first negative electrode slurry is coated on the surface of the first section of the negative electrode collector facing the pre-winding center, the second negative electrode slurry is coated on the surface of the second section of the negative electrode collector facing the pre-winding center, and the second negative electrode slurry is coated on the surface of the third section of the negative electrode collector facing the pre-winding center, and dried at 110°C to complete the single-sided coating of the negative electrode sheet; then, the second negative electrode slurry is coated on the surface of the first section of the negative electrode collector away from the pre-winding center, the second negative electrode slurry is coated on the surface of the second section of the negative electrode collector away from the pre-winding center, and the first negative electrode slurry is coated on the surface of the third section of the negative electrode collector away from the pre-winding center, and dried at 110°C to complete the double-sided coating of the negative electrode sheet. After that, cold pressing is performed, followed by auxiliary processes such as pole ear welding and adhesive tape pasting, and the entire preparation process of the double-sided coated negative electrode sheet is completed. Among them, the unit coating weight CW1 of the first negative electrode material layer is 130mg / 1540.24mm 2 The unit coating weight CW2 of the second negative electrode material layer is 130 mg / 1540.24 mm 2 The compaction density PD1 of the first negative electrode material layer is 1.62 g / cm 3 The compaction density PD2 of the second negative electrode material layer is 0.65 g / cm 3 The thickness H1 of the first negative electrode material layer is 52 μm, and the thickness H2 of the second negative electrode material layer is 130 μm. The specification of the negative electrode sheet is 1742 mm×67 mm, and the specification of the starting section of the negative electrode sheet is 80 mm×67 mm.
[0105] <Preparation of Electrolyte>
[0106] In a dry argon atmosphere, organic solvents ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are first mixed in a mass ratio of EMC:DEC=50:50 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) is added to the base solvent to dissolve and mix evenly to obtain an electrolyte, wherein the mass percentage of lithium salt lithium hexafluorophosphate (LiPF6) is 3% based on the mass of the electrolyte, and the balance is the base solvent.
[0107] <Diaphragm>
[0108] A polyethylene (PE) film with a thickness of 12 μm was used as the separator.
[0109] <Preparation of lithium-ion batteries>
[0110] The prepared diaphragm, negative electrode sheet, diaphragm, and positive electrode sheet are stacked in order, and pre-wound first to ensure that the diaphragm is between the negative electrode and the positive electrode, and at the same time ensure that the first section of the negative electrode collector is close to the center of the electrode assembly formed by pre-winding, and the two surfaces of the second section of the negative electrode collector are opposite to the positive electrode collector. After that, after winding, flattening, welding of the collector plate, shelling, bottom penetration welding, coding, vacuum drying, injection of electrolyte, sealing, high-temperature standing, and formation capacity, a lithium-ion battery can be obtained. Among them, the formation upper limit voltage is 4.3V, the formation temperature is 75°C, the number of windings of the electrode assembly is 25, and the width L of the electrode assembly is 40mm.
[0111] Example 1-2 to Example 1-6
[0112] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0113] Example 1-7 to Example 1-8
[0114] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. When the width L of the electrode assembly changes, the number of windings of the electrode assembly is adjusted so that the width L of the electrode assembly is as shown in Table 1.
[0115] Example 1-9 to Example 1-18
[0116] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. When the average particle size of the first negative electrode active material and the average particle size of the second negative electrode active material change, the grinding time of the particles is adjusted so that the values of D1 and D2 are as shown in Table 1.
[0117] Examples 1-19
[0118] Except that the second negative electrode material layer is provided on both surfaces of the third section in <Preparation of Negative Electrode Sheet>, the rest is the same as Example 1-1.
[0119] Examples 1-20
[0120] Except that the first negative electrode material layer is provided on both surfaces of the starting section of the first section in <Preparation of Negative Electrode Sheet>, the rest is the same as Example 1-1.
[0121] Example 2-1
[0122] Except for adding the additive vinylene carbonate in <Preparation of Electrolyte> and adjusting the relevant parameters according to Table 2, the rest is the same as Example 1-1. Among them, when the mass percentage of the additive in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of the lithium salt remains unchanged.
[0123] Example 2-2 to Example 2-4
[0124] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-1. When the mass percentage of the additive in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the ratio of each component in the base solvent remains unchanged, and the mass percentage of the lithium salt remains unchanged.
[0125] Comparative Example 1
[0126] Except that the first negative electrode material layer in <Preparation of negative electrode sheet> is prepared in the same manner as the second negative electrode material layer in Example 1-1, the rest is the same as Example 1-1.
[0127] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1 and Table 2.
[0128] Table 1
[0129] Note: “ / ” in Table 1 indicates no relevant preparation parameters.
[0130] From Example 1-1 to Example 1-20 and Comparative Example 1, it can be seen that by coating different negative electrode active materials on the negative electrode plate in a zoned manner, the risk of graphite exfoliation in the non-lithium intercalation area caused by co-intercalation of solvents in the non-lithium intercalation area of the lithium ion battery can be effectively reduced while taking into account both fast charging performance and high coulombic efficiency. In Comparative Example 1, only fast-charging graphite is coated on the negative electrode plate, and the demolding area of the non-lithium intercalation area of the lithium ion battery accounts for a large proportion during low-temperature cycling. However, the demolding area of the non-lithium intercalation area of the lithium ion batteries in Examples 1-1 to 1-20 accounts for a small proportion during low-temperature cycling, while taking into account both coulombic efficiency and charging rate, indicating that the lithium ion battery of the present application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by co-intercalation of solvents in the non-lithium intercalation area of the lithium ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0131] The type of coating material usually affects the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-3 and 1-4 that when the type of coating material is within the scope of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0132] The average thickness of the coating layer usually affects the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-5 and 1-6 that when the average thickness of the coating layer is within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0133] The values of L1 / L and L usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-7 to 1-10 that when the values of L1 / L and L are within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0134] The values of D1 and D2 usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Example 1-1, Example 1-11 to Example 1-12 that when the values of D1 and D2 are within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0135] The values of H1 / H2×100% and H2 usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-13 to 1-16 that when the values of H1 / H2×100% and H2 are within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by co-embedding of solvent in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0136] The values of CW1 and CW2 usually affect the coulombic efficiency, charging rate and demolding of non-lithium intercalation areas of lithium-ion batteries. It can be seen from Examples 1-1, 1-17 and 1-18 that when the values of CW1 and CW2 are within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0137] The values of PD1 and PD2 usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-13 to 1-18 that when the values of PD1 and PD2 are within the range of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by solvent co-intercalation in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0138] The arrangement positions of the first negative electrode material layer and the second negative electrode material layer usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 1-19 and 1-20 that when the arrangement positions of the first negative electrode material layer and the second negative electrode material layer are within the scope of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery accounts for a small proportion during low-temperature cycling, while taking into account both the coulombic efficiency and the charging rate, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by co-embedding of solvent in the non-lithium intercalation area of the lithium-ion battery while taking into account both fast charging performance and high coulombic efficiency.
[0139] Table 2
[0140] Note: “ / ” in Table 2 indicates no relevant preparation parameters.
[0141] The type and mass percentage of additives in the electrolyte usually affect the coulombic efficiency, charging rate and demolding of the non-lithium intercalation area of the lithium-ion battery. It can be seen from Examples 1-1, 2-1 to 2-4 that when the type and content of additives in the electrolyte are within the scope of this application, the demolding area of the non-lithium intercalation area of the lithium-ion battery is relatively small during low-temperature cycling, while the coulombic efficiency is high and the charging rate is large, indicating that the lithium-ion battery of this application can effectively reduce the risk of graphite exfoliation in the non-lithium intercalation area caused by co-embedding of solvents in the non-lithium intercalation area of the lithium-ion battery while taking into account fast charging performance and high coulombic efficiency.
[0142] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0143] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0144] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery, comprising an electrode assembly of a winding structure, the electrode assembly comprising a positive electrode sheet and a negative electrode sheet, wherein in the winding structure, along the reverse direction of the winding direction of the electrode assembly, the winding start end of the negative electrode sheet exceeds the winding start end of the positive electrode sheet; The positive electrode sheet includes a positive electrode current collector, the negative electrode sheet includes a negative electrode current collector, along the length direction of the unfolded negative electrode sheet and along the winding direction of the electrode assembly, the negative electrode current collector includes a first section and a second section connected in sequence, in the winding structure, the first section is a portion where at least one surface of the negative electrode current collector is not opposite to the positive electrode current collector, and the second section is a portion where both surfaces of the negative electrode current collector are opposite to the positive electrode current collector; in, The negative electrode sheet comprises a first negative electrode material layer and a second negative electrode material layer disposed on the surface of the negative electrode current collector, wherein the first negative electrode material layer comprises a first negative electrode active material, wherein the first negative electrode active material comprises at least one of artificial graphite or natural graphite; the second negative electrode material layer comprises a second negative electrode active material, wherein the second negative electrode active material comprises at least one of artificial graphite or natural graphite having a coating layer, wherein the coating layer comprises a coating material, wherein the coating material comprises one of a carbon material, an oxide or a polymer; The first negative electrode material layer is disposed on at least a portion of the surface of the first section facing the winding center of the electrode assembly, and the second negative electrode material layer is disposed on at least a portion of the surface of the second section facing the winding center of the electrode assembly.
2. The secondary battery according to claim 1, wherein The second negative electrode material layer is provided on at least part of the surface of the first section facing away from the winding center of the electrode assembly, the positive electrode sheet also includes a positive electrode material layer, and the positive electrode current collector is provided with the positive electrode material layer on the surface opposite to the second negative electrode material layer.
3. The secondary battery according to claim 1 or 2, wherein: The width of the electrode assembly is L mm, and along the length direction of the unfolded negative electrode sheet, the length of the first section is L1 mm, 1.5≤L1 / L≤2.5, 39.0≤L≤40.
5.
4. The secondary battery according to any one of claims 1 to 3, wherein The negative electrode current collector also includes a third section connected to the second section. Along the winding direction of the electrode assembly, the third section is a portion of at least one surface of the negative electrode current collector that is not opposite to the positive electrode current collector. The first negative electrode material layer is provided on at least a portion of the surface of the third section facing away from the winding center of the electrode assembly, and the second negative electrode material layer is provided on at least a portion of the surface of the third section facing the winding center of the electrode assembly.
5. The secondary battery according to claim 4, wherein The width of the electrode assembly is L mm, and along the length direction of the unfolded negative electrode sheet, the length of the third section is L2 mm, 1.5≤L2 / L≤3.0, 39.0≤L≤40.
5.
6. The secondary battery according to any one of claims 1 to 5, wherein In the winding structure, along the opposite direction of the winding direction, the first section includes a starting section that exceeds the winding starting end of the positive electrode collector, and along the thickness direction of the negative electrode sheet, both surfaces of the starting section are provided with the first negative electrode material layer.
7. The secondary battery according to any one of claims 1 to 6, wherein The carbon material includes at least one of carbon nanotubes, graphene, carbon fiber, carbon black or pyrolytic carbon, the oxide includes at least one of silicon dioxide, aluminum oxide, titanium oxide or zinc oxide, and the polymer includes at least one of polyacrylonitrile, polyaniline, polypyrrole, polyvinyl alcohol or polyimide.
8. The secondary battery according to any one of claims 1 to 7, wherein The average thickness of the coating layer is 10 nm to 100 nm.
9. The secondary battery according to any one of claims 1 to 8, wherein The average particle size of the first negative electrode active material is D1 μm, and the average particle size of the second negative electrode active material is D2 μm, where D1>D2.
10. The secondary battery according to claim 9, wherein 10≤D1≤30, 5≤D2≤20.
11. The secondary battery according to any one of claims 1 to 10, wherein The thickness of the first negative electrode material layer is H1 μm, the thickness of the second negative electrode material layer is H2 μm, 20%≤H1 / H2×100%≤60%, and 120≤H2≤140.
12. The secondary battery according to any one of claims 1 to 11, wherein The compaction density of the first negative electrode material layer is 0.93 g / cm 3 Up to 3.79g / cm 3 The compaction density of the second negative electrode material layer is 0.56 g / cm 3 Up to 0.76g / cm 3 .
13. The secondary battery according to any one of claims 1 to 12, wherein: The unit coating weight of the first negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 The unit coating weight of the second negative electrode material layer is 120 mg / 1540.25 mm 2 Up to 140mg / 1540.25mm 2 .
14. The secondary battery according to any one of claims 1 to 13, wherein The secondary battery also includes an electrolyte, the electrolyte includes an additive, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinylethylene carbonate or lithium bis(fluorosulfonyl)imide, and the mass percentage of the additive is 2% to 5% based on the mass of the electrolyte. 15 . An electronic device comprising the secondary battery according to claim 1 .
Citation Information
Cited By
Secondary battery and electric device
CN120432492A
Secondary battery and electronic device
CN120674563A